2018
DOI: 10.1186/s13049-017-0468-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality of acetaminophen poisoning: a nationwide population-based cohort study with 10-year follow-up in Taiwan

Abstract: BackgroundThe long-term mortality of acetaminophen (APAP) poisoning has not yet been well studied; hence, we conducted this study to gain understanding of this issue.MethodsWe conducted a nationwide population-based cohort study by identifying 3235 participants with APAP poisoning and 9705 participants without APAP poisoning in Taiwan between 2003 and 2012 in the Nationwide Poisoning Database and Longitudinal Health Insurance Database 2000. Participants with APAP poisoning and control subjects were compared fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Fifth, because we identified intoxication events based on ICD9 codes and the antidotes administered, there may have been some misclassification. However, previous studies based on similar databases showed reliable results [2,12,[47][48][49][50][51]. Our current research thus provides an overview of intoxication events in Taiwan between 2006 and 2013.…”
Section: Strengths and Limitationssupporting
confidence: 50%
“…Fifth, because we identified intoxication events based on ICD9 codes and the antidotes administered, there may have been some misclassification. However, previous studies based on similar databases showed reliable results [2,12,[47][48][49][50][51]. Our current research thus provides an overview of intoxication events in Taiwan between 2006 and 2013.…”
Section: Strengths and Limitationssupporting
confidence: 50%
“…ältesten Alters-gruppe. Dies steht im Einklang mit Huang et al, die einen Anstieg der Paracetamolvergiftungen im jüngeren Drittel ihrer Kohorte feststellten [7]. Die internationalen Unterschiede bei Substanzen, die zu akuten Vergiftungen führen, sind auffallend variierend, insbesondere wenn man den asiatischen und den europäischen Kontinent vergleicht: So gehört Kohlenmonoxid (CO) in einer Studie aus Hongkong zu den 4 häufigsten Substanzen, während in unserer Studie nur bei 11 Patienten (1,1 %) eine Vergiftung durch CO festgestellt wurde [10].…”
Section: Diskussionunclassified
“…In chronic conditions such as cancer pain and osteoarthritis, patients required long-term high dose use of APAP [2], at the same time, increasing the risk of APAP poisoning. Clinical studies indicated that high dose use of APAP for controlling chronic pain caused toxic effects in many organs as well as increased long-term mortality [3,4]. The major APAP metabolism organ is liver.…”
Section: Introductionmentioning
confidence: 99%